2021
DOI: 10.1111/imm.13349
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high‐sensitivity ELISA detecting IgG, IgA and IgM antibodies to the SARS‐CoV‐2 spike glycoprotein in serum and saliva

Abstract: Detecting antibody responses during and after SARS‐CoV‐2 infection is essential in determining the seroepidemiology of the virus and the potential role of antibody in disease. Scalable, sensitive and specific serological assays are essential to this process. The detection of antibody in hospitalized patients with severe disease has proven relatively straightforward; detecting responses in subjects with mild disease and asymptomatic infections has proven less reliable. We hypothesized that the suboptimal sensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…The published sensitivity and specificity of the test is similar to the saliva ELISA reported here (92% and 98%, respectively), but the slightly reduced specificity has a strong impact on the positive predictive value in diseases with low prevalence of salivary SARS-CoV-2 antibodies (13). Published studies on salivary SARS-CoV-2 IgG either used advanced immunoassay techniques [Luminex (11), immunoprecipitation systems (26)], in-house ELISAs, or repurposed commercial ELISAs for salivary IgG measurement (27,28). All work reported a consistent positive correlation between blood and saliva antibodies particularly for RBD specific IgG.…”
Section: Discussionsupporting
confidence: 60%
“…The published sensitivity and specificity of the test is similar to the saliva ELISA reported here (92% and 98%, respectively), but the slightly reduced specificity has a strong impact on the positive predictive value in diseases with low prevalence of salivary SARS-CoV-2 antibodies (13). Published studies on salivary SARS-CoV-2 IgG either used advanced immunoassay techniques [Luminex (11), immunoprecipitation systems (26)], in-house ELISAs, or repurposed commercial ELISAs for salivary IgG measurement (27,28). All work reported a consistent positive correlation between blood and saliva antibodies particularly for RBD specific IgG.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, it has been shown that patients with cancer are at a higher risk of morbidity and mortality following COVID-19 infection in comparison with healthy control groups (26). Exploring the associations between clinical manifestations of COVID-19 patients and serological responses, will provide us comprehensive insights toward understanding of the COVID-19 immunopathogenesis (28). There are several decisive factors which play a crucial role in the management of COVID-19 in patients with breast cancer such as: the viral load of the virus, the pathogenesis of virus, comorbidities, age, and subsequent mortality (29).…”
Section: Discussionmentioning
confidence: 99%
“…Development of this assay was undertaken by the authors (AMS, SEF, AMC, MTD, AGR) at the University of Birmingham in collaboration with The Binding Site. Detailed descriptions of this assay, including its construction, validation, and verification, have been published previously (Cook et al 2021; Faustini et al 2021). The assay demonstrates 98.3% (95% confidence interval [CI], 96.4%–99.4%) specificity and 98.6% sensitivity (95% CI, 92.6%–100%) in detecting serological responses to the SARS-CoV-2 spike glycoprotein following polymerase chain reaction (PCR)–positive, nonhospitalized, mild-to-moderate coronavirus disease 2019 (COVID-19).…”
Section: Methodsmentioning
confidence: 99%